Liquefaction of soybean protein and its effects on the properties of soybean protein adhesive. Issue 5 (4th September 2017) - Zhang, Leipeng; Zhang, Binghan; Fan, Bo; Gao, Zhenhua; Shi, Junyou
Abstract : Purpose: This paper aims to focus on the liquefaction of soybean protein to obtain a homogeneous protein solution with a high solid/protein content but low viscosity, which may improve the bond properties and technological applicability of soybean protein adhesive. Design/methodology/approach: The liquefactions of soybean protein in the presence of various amounts of sodium sulphite, urea and sodium dodecyl sulphate (SDS) are investigated, and their effects on the main properties of liquefied soybean protein and soybean protein adhesives are characterized by Fourier transform infrared spectroscopy (FT-IR), gel permeation chromatography (GPC), viscosity tracing and plywood evaluation. Meanwhile, the applicability of soybean protein adhesive composed of liquefied protein for particleboard is also investigated. Findings: Soybean protein can be effectively liquefied to form a homogeneous protein solution with a soybean protein content of 25 per cent and viscosity as low as 772 mPa.s; the addition of sodium sulphite, urea and SDS are beneficial for the liquefaction of soybean protein and have important effects on the technological applicability and water resistance of the obtained adhesive. The optimal liquefying technology of soybean protein is obtained in the presence of 1.5 Wt.% of sodium sulphite, 5 Wt.% of urea, 1.5 Wt.% of SDS and 3 Wt.% of sodium hydroxide. The optimal soybean protein adhesive has the desired water resistance in terms of the boiling-dry-boiling aged wet bond strength, which is up to 1.08 MPa higher than the required value (0.98 MPa) for structural use according to the commercial standard JIS K6806-2003. The optimal liquefied protein has the great potential to prepare particleboard. Research limitations/implications: The protein content of liquefied soybean protein is expected to further increase from 25 to 40 Wt.% or even higher to further reduce the hot-pressing cycle or energy consumption of wood composites bonded by soybean protein adhesives. Practical implications: The soybean protein adhesive composed of optimal liquefied protein has potential use in the manufacturing of structural-use plywood and has comparable applicability as a commercial urea-formaldehyde resin for the manufacturing of common particleboard. Social implications: Soybean protein adhesive is an environmentally safe bio-adhesive that does not lead to the release of toxic formaldehyde, and the renewable and abundant soybean protein can be used with higher value added by the application as wood adhesive. Originality/value: A novel liquefaction approach of soybean protein is proposed, and the soybean protein adhesive based on the liquefied protein is obtained with good technological applicability and desired bond properties that extend the applications of the soybean protein adhesive from interior plywood to particleboard and exterior or structural plywood.